Ask your own question, for FREE!
Mathematics
OpenStudy (anonymous):

If A, C, D are matrices does (AC^-1)^-1(AC^-1)(AC^-1)^-1(AD^-1) simplify to to A^2(C)(D)

8 years ago
OpenStudy (anonymous):

remembering that the inverse of the product of two matrices is the reverse product of the two inverses, then (AC^-1)^-1 = CA^-1 (CA^-1)(AC^-1) = CC^-1 = I, the unit matrix, so we are left with (AC^-1)^-1(AD^-1) = CA^-1AD^-1 = CD^-1

8 years ago
OpenStudy (anonymous):

I thought (AC^-1)^-1 = AC?

8 years ago
OpenStudy (anonymous):

Oh nvm that's where I went wrong, thank you!

8 years ago
Can't find your answer? Make a FREE account and ask your own question, OR you can help others and earn volunteer hours!